LAZDAI Lampung Sebagai Lembaga Keagamaan Dan Pemberdayaan Masyarakat - Suhandi, Suhandi (Universitas Islam Negeri Raden Intan Lampung, 2019)
The existence of religious institutions is a religious social institution that plays an important role in fostering the religious life of the community. The role is evident in the activities of providing education both formal and non-formal, as well as the activeness of religious institutions in charitable activities and fostering religious harmony. The community still feels the great benefits from the role of religious institutions in the formation of religious communities. Because the main task of religious institutions is to foster society with religious values; starting from the pattern of behavior, thoughts, patterns of life, then this will be closely related to the system of community development. Likewise with community development activities; it also seeks to empower people against aspects of life that are felt to be quite weak. The Amil Zakat Institution of the Charitable Area (LAZDAI) in Lampung is engaged in collecting and empowering zakat, infaq, shodakoh, waqf, and fidyah of donors. After conducting research using a qualitative approach, this institution has succeeded in empowering the Islamic community. Zakat funds are not only consumptive in nature, but are also empowered as mustahik business capital funds, scholarship funds, health funds, disaster victims' relief funds, and other social funds. While the inhibiting factors include: the limitations of human resources (HR) which resulted in socialization and information are still not affordable to all corners of Lampung, limited facilities and pre-supporting facilities such as vehicles, limited information facilities, and office facilities that are still minimal .